Corrosion Risk of RC Buildings After Ten Years the 2004 Tsunami in Banda Aceh - Indonesia. (2017) - Fonna, S.; Ridha, M.; Huzni, S.; Walid, W.A.; Mulya, T.T.D.; Ariffin, A.K.
Abstract: Banda Aceh was struck by the 2004 tsunami and submerged by seawater almost half a day and covered by mud monthly. The effect of the tsunami inundation for reinforce concrete (RC) buildings was the buildings become more susceptible to corrosion due to ion chloride intrusion. Hence, early failure might happen to the buildings because of rebar corrosion. It can be worsening by the earthquakes that frequently occur in the region. Thus, the corrosion monitoring for the buildings become important. The previous monitoring was taken on 2009 and 2012 and found that the corrosion level of the buildings already at intermediate to high risk. The objective of this study is to conduct corrosion risk monitoring for RC building after ten year the 2004 tsunami in Banda Aceh city, Indonesia. The monitoring was conducted using half-cell potential mapping technique that refers to ASTM C876 and performed in 2015. Three building in tsunami-affected area were chosen for the monitoring. The monitoring results show that the corrosion levels for the buildings located in the 2004 tsunami-affected area were at intermediate to high risk. Comparing the results with those on 2009 and 2012 indicated that the corrosion risk level tend to increase. Therefore, the regular monitoring and repairing are important to be carried out in order to hinder sudden failure of the buildings.